Pengaruh Live Streaming dan E-Wom terhadap Purchase Intention Produk Skintific Melalui Tiktok Shop dengan Consumers Attitude sebagai Variabel Mediasi: Survey pada Mahasiswa Kota Solo - Yugo Nabila Putri; Nabila Putri Amaria; Diyah Ayu Wulandari; Leo Agung Saputra; David Trita Perdana; Nadiya Fikriyatuz Zakiyah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The development of digital technology has changed consumer behavior in making purchasing decisions, including the increasing use of social media as a means of online shopping. This study aims to analyze the effect of live streaming and E-Wom on purchase intention of Skintific products through TikTok Shop with consumers attitude as a mediating variable. The population in this study were students in Solo City. The sample used and tested was 100 respondents, using the simple random sampling method to determine relevant respondents and tested using SPSS software. The data collection method in this study used a questionnaire and the data analysis techniques used were descriptive statistical analysis, multiple linear regression analysis, t test, f test, sobel test, and coefficient of determination test. The results of this study indicate that live streaming and consumers attitude have a positive and significant effect on purchase intention, while E-Wom has no significant effect on purchase intention in purchasing Skintific products through the TikTok Shop application..